Kerusakan Bearing dan Electromotor pada Pompa Air Laut di Atas Kapal MT. Anggraini Excellent - Angga Pratama, Riesky Yoga; Didik Dwi Suharso; Anicitus Agung Nugroho (Indonesian Journal of Marine Engineering, 2025)
The MT Anggraini Excellent ship was sailing from Balikpapan to Samarinda when an alarm sounded during the watch. The main engine jacket cooling system indicated a high temperature of 88º C. Measures were taken to reduce the rpm (slowhead) and report the condition of the main engine. A request was made to stop the engine to inspect the cooling system. Using a qualitative descriptive method, data was collected through observations, temperature readings, pressure measurements, maintenance records, and interviews. The factors causing and the impacts of the seawater pump failure were identified. Maintenance and repair actions for the seawater pump were implemented to support the operation of the main engine. The collected data will be analyzed using the fishbone approach and processed with triangulation techniques to identify the factors causing the seawater pump electromotor failure and address overheating in the main engine. The research results indicate that the cause of bearing damage is exceeding the running hours limit of 2,750 hours, with an average insulation test on the electromotor of 10MΩ, and a decrease in pump pressure of 1.5 kg/cm² from the normal condition of 3 kg/cm² due to mechanical seal damage and a dirty seachest. The bearings, the three-phase 60 Hz 440 V 55 kW electric motor, and the mechanical seal were replaced. It is recommended to perform regular maintenance on the electric motor and pump in accordance with the PMS (Plan Maintenance System). Ensuring the availability of spare parts, electric motors, and seawater pumps is essential to maintain operational efficiency during maintenance.